NR2B-DAPK1-P53 mediated hippocampal cell death following monosodium glutamate ingestion and interventions with luteolin, caffeic-acid and phoenix dactylifera - Ibiyeye, Ruqayyah; Imam, Aminu; Adana, Misturah; Sulaimon, Fatimo; Ajao, Moyosore (Nepal Journal of Neuroscience, 2022)
Introduction: Glutamate is the major excitatory neurotransmitter in the brain, but its accumulation potentiates excitotoxicity. In most food seasonings is the monosodium glutamate (MSG), whose over ingestion have been reported with glutamate-like neurotoxicity, thus, this study investigated the efficacy of Phoenix dactylifera and two of its phytochemicals MSG hippocampal toxicity. Materials andMethods: Forty-eight male Wistar rats were randomly allocated to eight groups of six rats each (n=6). The control received normal saline, group 2 received 4 g/kg MSG, groups 3 to 5 received 4 g/kg MSG followed by 100 mg/kg caffeic-acid, 100 mg/kg luteolin and 500 mg/kg Phoenix dactylifera, while groups 6 to 8 received the above agents first followed by 4 g/kg MSG orally for 21 days. 24 hours after the last ingestion, the rats were euthanized and hippocamapal tissue was removed and processed for GluN2B, DAPK1 and p53 immuno histochemical staining.Results: Repeated MSG ingestions caused high expressions of GluN2B, DAPK1 and p53 in the hippocampus of the exposed rats suggestive of an apoptotic cascades along the NR2B-DAPK1-P53 neuronal death pathway. Pre- or post- treatment with caffeic-acid, luteolin or Phoenix dactylifera markedly reduced the hippocampal expressions GluN2B, DAPK1 and p53.Conclusion: Phoenix dactylifera and its flavonoids are capable of downplaying the activities GluN2B, DAPK1 and p53 in MSG toxicity, thereby preventing hippocampal cell death.